2015
DOI: 10.1117/1.jmi.2.2.024503
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphometry of primary brain tumors by magnetic resonance imaging

Abstract: Abstract. Magnetic resonance imaging is a technique for the diagnosis and classification of brain tumors. Discrete compactness is a morphological feature of two-dimensional and three-dimensional objects. This measure determines the compactness of a discretized object depending on the sum of the areas of the connected voxels and has been used for understanding the morphology of nonbrain tumors. We hypothesized that regarding brain tumors, we may improve the malignancy grade classification. We analyzed the value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Several studies have suggested that morphological measures may help to classify and characterize brain tumors [17,18]. To quantify the morphology of the spheroids in the 3D cultures, we determined the circularity of the spheroids formed in the biospheres.…”
Section: Mathematical Analysis Of Spheroid Growth and Morphologymentioning
confidence: 99%
“…Several studies have suggested that morphological measures may help to classify and characterize brain tumors [17,18]. To quantify the morphology of the spheroids in the 3D cultures, we determined the circularity of the spheroids formed in the biospheres.…”
Section: Mathematical Analysis Of Spheroid Growth and Morphologymentioning
confidence: 99%
“…[12] presentan un estudio de morfometría 3D para poder diferenciar entre glioblastomas multiformes y metástasis a partir de imágenes por tensores de difusión. Nuestro grupo de investigación ha realizado un análisis morfométrico 3D en cuanto a la compacidad discreta (C d ) como descriptor de forma entre gliomas de diversos grados de malignidad, teniendo como resultados una primera discriminación entre ellos significativa [13] .…”
Section: Antecedentesunclassified
“…The development of computational methods to objectively extract insights out of imaging data is an ongoing challenge [34]. For instance, current tumor guidelines to assess tumor progression in the clinical setting are often limited to one- or two- dimensional orthogonal measurements; standards like the Revised Assessment in Neuro-Oncology (RANO) [5] attempt to quantify lesions by assigning different evaluation options depending on these linear measurements (longest diameter measures) to ascertain significant change.…”
Section: Introductionmentioning
confidence: 99%